Use of hydroxychloroquine and interferon alpha-2b for the prophylaxis of COVID-19. (November 2020) - Yang, Alexander; Yang, Charlotte; Yang, Bing
Abstract: The ongoing pandemic of COVID-19 infection demands efforts to reduce spread. In order to eradicate an infectious disease, a method of prevention with low social cost is the most effective way. While we wait for new therapies and a vaccine, we are proposing a solution based on the existing knowledge in biomedical sciences. Here we propose to use low doses of hydroxychloroquine (50–100 mg daily orally) and intranasal interferon alpha-2b (IFN α-2b) spray (0.5 × 10 6 IU twice daily) for the prophylaxis of COVID-19. Although there are ongoing clinical trials to test the efficacy of hydroxychloroquine for prophylaxis, there has not been any proposal to test the efficacy of IFN α-2b together with hydroxychloroquine to increase protection against COVID-19. Since the two act on two different mechanisms, we strongly believe that the two could have additive effects in prophylaxis against COVID-19. We recommend using a randomized control study to prove efficacy and safety.